A Clinical Study to Evaluate the Effectiveness of Kokilakshadhi Kwatha in the Management of Vatakantaka (Plantar Fasciitis) - Kripa D; Waheeda Banu (International Journal of Ayurveda and Pharma Research, 2021)
Pain is a symptom which alters our day to day activities, affecting the quality of life. One among such pain is, pain in the heel, which causes difficulty in walking and in turn disturbs daily routines. Plantar fasciitis is most common cause of heel pain in adults. It is estimated that 1 in 10 people may experience inferior heel pain during their life time. Signs and symptoms of Vatakantaka resembles with Plantar fasciitis according to modern paralines. Treatment Modalities according to modern science is NSAIDS, toe stretching, corticosteroid injections, extracorporeal shock wave therapy and surgical correction are the indicated treatments. Analgesics have been used in practice by modern practitioners to give immediate relief to patients from pain. And modern medicine has a huge number of the drug for pain management but they impact body with serious side effects. Therefore there is a large scope of finding a treatment for Vatakantaka So in this study Kokilakshadi Kwatha explained in Yogaratnakara is considered. The study is divided into four sections as Disease review, Drug review, Pharmaceutical study and clinical study. Methods: The outcome of Kokilakshadi kwatha is evaluated clinically on minimum of 30 patients. Kokilakshadi kwatha was given for 21 days. The lab test and clinical analysis were done as per requirement for the assessment. Evaluation of parameters of the disease like Pain and Tenderness were done before treatment, after 11 days and after 21days. Results: As a result, Out of 30 patients, highly significant results (p<0.001) were obtained with respect to pain (93.3%) and tenderness (60%). Conclusion: Kokilakshadi Kwatha showed good results in reduction of signs and symptoms of Vatakantaka. The statistical analysis also supported this by concluding that the improvement after treatment is highly significant.